Comparison of auditory temporal resolution between monolingual Persian and bilingual Turkish-Persian individuals. (April 2013) - Omidvar, Shaghayegh; Jafari, Zahra; Tahaei, Ali Akbar; Salehi, Masoud
Abstract Objective: The aims of this study were to prepare a Persian version of the temporal resolution test using the method of Phillips et al (1994) and Stuart and Phillips (1996), and to compare the word-recognition performance in the presence of continuous and interrupted noise as well as the temporal resolution abilities between monolingual (ML) Persian and bilingual (BL) Turkish-Persian young adults. Design: Word-recognition scores (WRSs) were obtained in quiet and in the presence of background competing continuous and interrupted noise at signal-to-noise ratios (SNRs) of − 20, − 10, 0, and 10 dB. Study sample: Two groups of 33 ML Persian and 36 BL Turkish-Persian volunteers participated. Results: WRSs significantly differed between ML and BL subjects at four sensation levels in the presence of continuous and interrupted noise. However, the difference in the release from masking between ML and BL subjects was not significant at the studied SNRs. Conclusions: BL Turkish-Persian listeners seem to show poorer performance when responding to Persian words in continuous and interrupted noise. However, bilingualism may not affect auditory temporal resolution ability.